Carbon sequestration: pulling off an ecological hat-trick? - Touré, Assise (Technical Centre for Agricultural and Rural Cooperation, 2006)
Assise Touré explains how remote sensing and computer simulations are helping West Africa to take advantage of the Clean Development Mechanism.